The Effect of Compensation and Motivation on Employee Performance in PT. Sarana Pembangunan Palembang Jaya (PT. SP2J) - Dian Mellany; Luis Marnisah; M. Kurniawan DP (International Journal of Marketing & Human Resource Research, 2023)
This study aims to determine whether there is an effect of compensation and motivation on the performance of employees at  PT. Sarana Pembangunan Palembang Jaya (PT. SP2J) Oil and Gas Business Unit of Palembang City. The number of samples in this study was 45 employee respondents. data collection techniques in this study by means of a questionnaire. Data analysis using multiple linear regression analysis. Based on the results of testing with SPSS 21, compensation on employee performance has a significant effect between compensation and motivation on employee performance. Research is expected to assist Companies in affected compensation and motivation variables on employee performance